Art therapy as a comprehensive complementary treatment for Parkinson’s disease - Ettinger, Tom; Berberian, Marygrace; Acosta, Ikuko; Cucca, Alberto; Feigin, Andrew; Genovese, Danilo; Pollen, Travis; Rieders, Julianne; Kilachand, Rohita; Gomez, Clara; Kaimal, Girija; Biagioni, Milton; et al. (Frontiers in Human Neuroscience, 2023)
Parkinson’s disease (PD) is the second most prevalent neurodegenerative disease. Complementary and alternative therapies are increasingly utilized to address its complex multisystem symptomatology. Art therapy involves motoric action and visuospatial processing. Furthermore, art therapy facilitates patients’ engagement with deep and multilayered psychological conflicts. Once these conflictual materials are externalized in a tangible medium, they can be faced, explored, verbalized, understood, integrated, and resolved, promoting overall biopsychosocial growth. Herein, a mixed methods study evaluates the outcomes of 20 sessions of group art therapy for 42 participants with mild to moderate PD through an arts-based assessment that was developed to match the treatment modality for maximum sensitivity. Specifically, the House-Tree-Person PD Scale (HTP-PDS) was developed and implemented to assess motor and visuospatial processing – core PD symptoms – as well as a broad array of biopsychosocial variables including cognition, affect/mood, motivation, self, interpersonal functioning, and creativity, both before and after art therapy treatment. It was hypothesized that art therapy would ameliorate core PD symptoms and that this would correlate with improvements in all other variables. The results, comparing pre- and post-assessments, demonstrate significant improvement across all symptoms and variables, though causality was indeterminate. This research supports the utilization of art therapy for holistic treatment of PD and supports the use of arts-based assessment, such as the HTP-PDS, for nomothetic research purposes.